Protective effects of diet containing rutin against trichlorfon-induced muscle bioenergetics disruption and impairment on fatty acid profile of silver catfish Rhamdia quelen - Baldissera M.D. (2020)
© 2020 Elsevier Inc.Trichlorfon is an organophosphate insecticide that is widely used on fish farms to control parasitic infections. It has been detected in freshwater ecosystems as well as in fishery products. There is a growing body of evidence to suggest that certain feed additives may reduce or prevent pesticide-induced toxicity in fish. The aim of the present study was to determine whether acute exposure to trichlorfon would alter bioenergetic homeostasis and alter fatty acid profiles in muscles of silver catfish (Rhamdia quelen). We also sought to determine whether rutin prevents or reduces these effects. Cytosolic and mitochondrial creatine kinase (CK) and activities of complexes II-III and IV in muscle were significantly inhibited by exposure to 11 mg/L trichlorfon for 48 h compared to effects in the unexposed group. Total content of polyunsaturated fatty acids (omega-3 and omega-6) were significantly lower in muscle of silver catfish exposed to 11 mg/L trichlorfon for 48 h than in the unexposed group. Addition of 3 mg rutin/kg feed increased CK activity and prevented inhibition of complex IV activity, as well as preventing all alterations of muscle fatty acid profiles elicited by exposure to trichlorfon. No significant differences were observed between groups with respect to muscle adenylate kinase or pyruvate kinase activities, as well as total content of saturated and monounsaturated fatty acids. Our findings suggest that exposure (48 h) to 11 mg trichlorfon/L water inhibits cytosolic and mitochondrial CK activity in muscle. Trichlorfon also affects activities of complexes II-III and IV in respiratory chain, with important consequences for adenosine triphosphate production. The pesticide alters fatty acid profiles in the fish and endangers human consumers of the product. The most important finding of the present study is that inclusion of rutin improves bioenergetic homeostasis and muscle fatty acid profiles, suggesting that it reduces trichlorfon-induced muscle damage.© 2020 Elsevier Inc.The main finding is that rutin can be used to reduce trichlorfon-induced muscle toxicity, representing a suitable alternative to improve human and fish health.